Pengaruh Penerapan E-Government (SPBE) Melalui Penggunaan Aplikasi “Sakedap”Terhadap Efisiensi dan Efektivitas Pelayanan Publik Dalam Mewujudkan Smart City (Studi Kasus Pelayanan Publik di Kecamatan Cileunyi, Kabupaten Bandung) - Amjad Aushap; Muhammad Lutfi Naufal; Muhammad Nurjaman; Ivan Darmawan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Continuing public services using applications and information technology is the bandung regency regional government's effort to implement E-government to increase the smoothness of providing services to the community by using the sakedap application (integrated population service system) in making KTPs which influences the effectiveness of the bureaucracy and to maximize services public and bureaucracy by implementing E-Government with adequate facilities and infrastructure. This aims to increase community participation, information transparency (Open Government), and decision making. The purpose of this article is to find out the influence of using this application for public services on the effectiveness of service implementation in Cileunyi District and the factors that influence public services. The method used is a qualitative method by collecting observational data, statistical data and literary data explored in printed and electronic media, then the data goes through a process of analysis, triangulation, presentation and data verification. The data analysis stages consist of data exploration and classifying data, interpreting and describing data, developing data and presenting data in the form of text and images about the subject matter. The theory used is based on the Stages of E-Government (Hiller Bélanger, 2001), namely Information, Two-Way Communication, Transaction, Integration, and Participation. The research results show that the use of the "Sakedap" application has an influence on the effectiveness and efficiency of public services in Cileunyi District with several driving efforts, namely socialization, bureaucratic organizational management, provision of facilities, infrastructure and human power, especially in providing technological facilities for safe data storage and Hassle-free administration and transactions.